Online teaching and learning: COVID-19 Special Issue - Alison J Fields; Maggie Hartnett (Flexible Learning Association of New Zealand, 2020)
JOFDL is supporting the education community worldwide during the COVID-19 pandemic by making available a collection of high impact, previously-published articles on online and eLearning in a single issue. This resource adds to the online teaching and learning ideas, inspiration, information and application for educators in these unprecedented times.